2009
DOI: 10.1123/jpah.6.s1.s141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kenz Lifecorder Versus Actigraph Physical Activity Output in Free-Living Conditions

Abstract: Background:The Kenz Lifecorder EX (KL) is a relatively new, moderately priced, user friendly accelerometer that tracks step counts and time spent in various intensity classifications. Thus, the KL is an attractive instrument for researchers and the public. However, there is limited research comparing the KL’s output to other accelerometers during free-living conditions. Therefore the purpose of this study was to compare KL versus ActiGraph (AG) outputs of step counts and time spent in various intensity classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, our findings were not consistent with McClain's results. Although the study was conducted in adults, the results of comparison of the ActiGraph and Lifecorder step counts were not consistent with the reports of higher ActiGraph [25] and higher Lifecorder [26]. Abel et al [26] have reported that these discrepancies may be owing to the differences in Acti-Graph models.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, our findings were not consistent with McClain's results. Although the study was conducted in adults, the results of comparison of the ActiGraph and Lifecorder step counts were not consistent with the reports of higher ActiGraph [25] and higher Lifecorder [26]. Abel et al [26] have reported that these discrepancies may be owing to the differences in Acti-Graph models.…”
Section: Discussionmentioning
confidence: 73%
“…Although the study was conducted in adults, the results of comparison of the ActiGraph and Lifecorder step counts were not consistent with the reports of higher ActiGraph [25] and higher Lifecorder [26]. Abel et al [26] have reported that these discrepancies may be owing to the differences in Acti-Graph models. The difference between the present study and McClain's study (ActiGraph GT1M, Lifecorder EX) may be owing to the different models of ActiGraph and Lifecorder.…”
Section: Discussionmentioning
confidence: 73%
“…Energy intake and dietary composition were evaluated using a 3-day dietary log. The mean physical activity level was estimated over 7 days with an accelerometer before or after the experimental day (Lifecorder; Suzuken, Nagoya, Japan) [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…(32, 33) Participants in both groups wore the accelerometer for at least 10-hours for a period of seven days at each of the assessment time points and they were directed to keep an adherence diary giving details as to when the monitor was worn and taken off during the day. Participants wore the accelerometers during their structured exercise time at the five-month time point and were instructed to maintain their regular level of physical activity outside of structured exercise.…”
Section: Methodsmentioning
confidence: 99%